Demand for fish and meat products with habit formation - Raja Abdullah, Nik Mustapha (Universiti Putra Malaysia, 1994)
An Almost Ideal Demand System with habit formation was estimated for fish and four meat products in Malaysia for the period of 1960-1990. It was found that these was pervasiveness of habit formation for fish, chicken and pork but not beef and mutton. Fish and other meat products were found to be necessities and demand for chicken was price elastic but demand for fish, pork, and beef was less responsive to their price change. Fish substitutes for chicken and pork but all meat products were complementary to each other.